2016
DOI: 10.1007/s11102-016-0733-2
|View full text |Cite
|
Sign up to set email alerts
|

Clinical prevalence and outcome impact of pituitary dysfunction after aneurysmal subarachnoid hemorrhage: a systematic review with meta-analysis

Abstract: Neuroendocrine dysfunction is common after aSAH, but these abnormalities have not been shown to consistently impact outcome in the data available. There is a need for well-designed prospective studies to more precisely assess the incidence, clinical course, and outcome impact of pituitary dysfunction after aSAH.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
25
5

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(36 citation statements)
references
References 67 publications
(104 reference statements)
6
25
5
Order By: Relevance
“…In the present study, we observed higher HCCs in the aSAH group. Accordingly, the present data are at odds with studies showing that patients with aSAH have suffered from hypopituitarism [14,36] and tended to have a lower morning overall cortisol output [16]. However, previous studies have also shown that compared to healthy controls, aSAH patients had a higher CAR as measured by the AUCi [16].…”
Section: Discussioncontrasting
confidence: 73%
See 1 more Smart Citation
“…In the present study, we observed higher HCCs in the aSAH group. Accordingly, the present data are at odds with studies showing that patients with aSAH have suffered from hypopituitarism [14,36] and tended to have a lower morning overall cortisol output [16]. However, previous studies have also shown that compared to healthy controls, aSAH patients had a higher CAR as measured by the AUCi [16].…”
Section: Discussioncontrasting
confidence: 73%
“…However, our findings add to the existing literature by providing preliminary evidence that high HCC levels can be used as a biomarker for poor psychological functioning among aSAH populations. This finding is important as researchers were not able to correlate assessments of pituitary hormone dysregulation with the outcomes of aSAH patients in previous studies [36]. …”
Section: Discussionmentioning
confidence: 96%
“…Subarachnoid hemorrhage (SAH) is an important cause of morbidity and mortality, and there is evidence that SAH may adversely affect pituitary function in both the acute and chronic phases (30,31). The prevalence of endocrine dysfunction caused by SAH ranges from 0 to 55% (31,32).…”
Section: Subarachnoid Hemorrhage (Sah)mentioning
confidence: 99%
“…The prevalence of endocrine dysfunction caused by SAH ranges from 0 to 55% (31,32). Isolated pituitary hormone deficiencies are more frequently found than multiple.…”
Section: Subarachnoid Hemorrhage (Sah)mentioning
confidence: 99%
“…While it is well known that the bleeding itself and hospital complications substantially contribute to these deficits [2,3], early identification of patients at high risk remains difficult. Some of the typical neuropsychological deficits after SAH resemble clinical symptoms of hypopituitarism [4], which is commonly observed in the acute and subacute phase after SAH [5][6][7][8]. Potential pathophysiological mechanisms resulting in endocrine dysfunction include direct compression of the hypothalamic-pituitary complex by the aneurysm itself, intracranial hypertension, compromised perfusion during initial circulatory arrest after SAH with subsequent ischemic injury, hydrocephalus, and iatrogenic causes through pharmacological treatment or procedure related injuries [5,9].…”
Section: Introductionmentioning
confidence: 99%